(untitled) (Biological Sciences - PJSIR, 2009)
Studying the effect of different sugar concentration of beet molasses on citric acid accumulation in batch fermentation, 150 g/litre sugar concentration was found to be optimal for maximum citric acid production (27.25±2.35 g/ litre) using Aspergillus niger M-101. Yp/x value for product formation increased with increase in sugar concentration through out the study. Qp value for citric acid production also increased with increase in sugar concentration and reached the maximum (0.141 g/1itre/h) at 150 g/litre sugar concentration but with further increase in sugar concentration, the value decreased. When culture was grown at different substrate concentrations, the kinetic parameters monitored for Yx/s, Yp/s and Yp/x, Qp, Qs and qp showed significant enhancement (p £ 0.05) in citric acid production as well as biomass growth.